Best Answer

This can be factored as (x+3)(x+2). (To do this factoring, in this case you look for two numbers that, when multiplied, give 6, and when added, give 5.)

Study guides

☆☆

Q: X2 plus 5x plus 6x equals?

Write your answer...

Submit

Still have questions?

Related questions

x2 + 5x - 6x = x2 - x = x(x - 1) which is zero when x = 0 or x = 1

x(x2+5x+6)

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

x2+6x+9 = x+3 x2+6x-x+9-3 = 0 x2+5x+6 = 0 Solve by factoring or with the help of the quadratic equation formula: (x+3)(x+2) = 0 Therefore: x = -3 or x = -2

Assuming you mean x squared plus 5x squared... the answer is 6x squared.

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)

(X + 5)(X + 1) FOIL this. X2 + 1X + 5X + 5 Gather terms. X2 + 6X + 5 ----------------------------those were the factors

x2 - 5x - 6 = x2 - 6x + x - 6 = x(x - 6) + 1(x - 6) = (x - 6)(x + 1)

x2 + 5x - 6 = x2 + 6x - x - 6 = x(x + 6) - 1(x + 6) = (x - 1)(x + 6)

x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1

x2 + 6x + 12 = 0 x2 + 6x + 9 = -3 (x + 3)2 = -3 x + 3 = ± √-3 x = -3 ± i√3

(3, -21)